Impact of adjunctive tirofiban administration on myocardial perfusion and mortality in patients undergoing primary angioplasty for ST-segment elevation myocardial infarction - De Luca, Giuseppe; Smit, Jaap J.; Ernst, Nicolette; Suryapranata, Harry; Ottervanger, Jan Paul; Hoorntje, Jan C. A.; Dambrink, Jan-Henk E.; Gosslink, Marcel A. T.; de Boer, Menko-Jan; van’t Hof, Arnoud WJ (Thrombosis and Haemostasis, 2005)
Several studies have shown that suboptimal myocardial perfusion may be observed despite optimal epicardial recanalisation in patients undergoing primary angioplasty for ST-segment elevation myocardial infarction (STEMI), resulting in unfavourable outcome. The aim of the current study was to evaluate the benefits in myocardial perfusion and mortality from adjunctive tirofiban administration in patients undergoing primary angioplasty for (STEMI). A total of 1,969 patients with STEMI treated by primary angioplasty represent the population of the current study. All clinical, angiographic and follow-up data were prospectively collected. Tirofiban was administrated in 481 patients (24.4%) (all before angioplasty). Tirofiban was associated with less distal embolisation (11.7% vs 16.1%, p = 0.048), better postprocedural MBG 3 (50.9% vs 39.7%, adjusted p < 0.0001) and a significant reduction in 1-year mortality (3% vs 6.4%, adjusted p = 0.045). The benefits in mortality were confirmed in all subgroups identified according to the quartiles of the propensity score. This study shows that, when compared to control group, adjunctive tirofiban before primary angioplasty for STEMI is associated with better myocardial perfusion and a reduction in 1-year mortality.
Keywords: Mortality; primary angioplasty; myocardial infarction; tirofiban; myocardial perfusion